The Mediating Role of Self-Regulated Learning in the Relationship between Technical Self-Efficacy and Satisfaction with E-Learning Courses among Learners in the Optimal Investment Program for Educational Cadres at Northern Border University - Abdul-Redha Jawad Hayal (Journal of College of Education, 2024)
This current study aimed to investigate the correlational relationship between technical Self-Efficacy, self-regulated learning, and satisfaction with e-learning courses, as well as to unveil the mediating role of self-regulated learning in the relationship between technical Self-Efficacy and satisfaction with e-learning courses. The study sample consisted of 134 participants enrolled in the Optimal Investment Program for Educational Cadres at Northern Border University. The study utilized three questionnaires: The Technical Self-Efficacy Questionnaire, the Self-Regulated Learning Questionnaire, and the E-Learning Courses Satisfaction Questionnaire. The study's results indicated the predictive capability of technical Self-Efficacy and self-regulated learning in relation to satisfaction with e-learning courses. Furthermore, it revealed that self-regulated learning serves as a mediating factor in the relationship between technical Self-Efficacy and satisfaction with e-learning courses
Keywords: Self-regulated learning; Technical Self-Efficacy; Learner satisfaction; E-learning courses; Northern Border University